PENGARUH KESADARAN MEREK, ASOSIASI MEREK, PERSEPSI KUALITAS DAN LOYALITAS MEREK TERHADAP PROSES PENGAMBILAN KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA V-IXION - Arif Fadhilah (Universitas Mercu Buana, 2015)
Abstract: The study sought to establish and analyze the impacts of brand awareness, brandassociations, perceived quality and brand loyalty toward purchase decision-making process of Yamaha V-Ixion both partially and simultaneously. This statistic parametric study adopted a quantitative method that used a multiple linear regression in which the data were processed by program. The population used in this study are all users of Yamaha V-Ixion in Jakarta whose number is unknown. The sample was 80 users of Yamaha V-Ixion located in West Jakarta Municipality. A structured questionnaire with Likert scale was used to collect data which consisted of 34 questions arranged based on indicators and dimensions derived from each independent variables. Findings of this study showed that brand awareness, perceived quality and brand loyalty had significant effect in partially toward purchase decision-making process of Yamaha V-Ixion. Furthermore, brand awareness, perceived quality and brand loyalty had significant effect in simultaneously toward purchase decision-making process Yamaha V-Ixion.Keywords: Brand Awareness, Brand Association, Perceived Quality, Brand Loyalty and purchase decision-making process